1990
DOI: 10.1161/01.str.21.5.765
|View full text |Cite
|
Sign up to set email alerts
|

Study of the elastic skeleton of intracranial arteries in animal and human vessels by scanning electron microscopy.

Abstract: We studied the elastic skeleton of major cerebral arteries in rats, monkeys, and one human using scanning electron microscopy after hot formic acid extraction followed by freeze-drying. For comparison, we also examined the thoracic aorta and femoral artery of rats. The cerebral arteries of rats had one distinct internal elastic lamina connected to the thin adventitia with sponge-like medial elastic tissue. This internal elastic lamina had fenestrations, which we found to be less frequent in cerebral arteries t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Although the nature and significance of the folds are still unclear, their site and size indicate that they are located between endothelial cells. 5 The area of loss of the folds corresponds to the area of degeneration of endothelial cells in the early stage of aneurysmal formation 8 and appears to correspond to the degenerative change of endothelial cells. Medial sponge-like structures are also located between smooth muscle cells and are destroyed during the course of degeneration of these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the nature and significance of the folds are still unclear, their site and size indicate that they are located between endothelial cells. 5 The area of loss of the folds corresponds to the area of degeneration of endothelial cells in the early stage of aneurysmal formation 8 and appears to correspond to the degenerative change of endothelial cells. Medial sponge-like structures are also located between smooth muscle cells and are destroyed during the course of degeneration of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…- 4 The results of our previous study of normal cerebral arteries under scanning electron microscopy after hot formic acid extraction 5 showed that the internal elastic lamina was not the sole element, but a part of the complicated architecture of the elastic skeleton. Based on these observations, we considered that the process of various vascular pathologies might be re-evaluated by analyzing morphologic changes of the elastic skeleton in cerebral arteries.…”
mentioning
confidence: 99%
“…The ECM is a dynamic network of proteins and proteoglycans that is essential for structural maintenance in many tissues and relies on a balance between synthesis and degradation of ECM proteins. The content and three-dimensional organization of elastin fibers, an essential component of the ECM of vessel walls, was found to be altered in the wall of cerebral aneurysms [6]. In a gene expression analysis of a single IA, elastin was among the most abundantly expressed tags, indicating that in this IA significant tissue remodeling was taking place [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the present article, the term "subendothelial" refers to the region just below the endothelial surface but on the adluminal side of the IEL. Similarly, in the intracranial arteries of the rat and human, the IEL consists of a double layer, in this case associated with a honeycomb-like network of fine elastic fibers (48). IEL splitting and axially aligned fibrils have also been noted in pathological states, such as the formation of intimal pads or cushions and hypertension (39,44).…”
mentioning
confidence: 98%